Skrining dan Edukasi Kesehatan Metabolik melalui Pemeriksaan Profil Lipid pada Masyarakat Kelurahan Kota Bambu, Jakarta Barat: Metabolic Health Screening and Education through Lipid Profile Testing in the Bambu Village Community, West Jakarta - Triyana Sari; Alexander Halim Santoso; Daniel Goh; Fidelia Alvianto; Syilvia Cendy Enike (Akademi Keperawatan Bunda Delima, 2026)
Introduction: Lipid profile is an essential parameter in assessing metabolic health and cardiovascular risk. Total cholesterol, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) are the main components used to evaluate lipid metabolism balance, which is often disrupted in urban populations. This community service activity aimed to increase public awareness of metabolic health through education and simple screening of lipid profiles. Method: The program was conducted in Kelurahan Kota Bambu, West Jakarta, in June 2025, involving 168 participants across various age groups. Lipid profile measurements were performed using the Nesco BL-101 5in1 Lipid Panel Monitoring System, and interactive educational sessions were provided to promote healthy diet and dyslipidemia prevention. Results: The results showed that the average total cholesterol level was 208.24 mg/dL, HDL was 51.15 mg/dL, and LDL was 122.11 mg/dL. Classification revealed that most participants had high total cholesterol and LDL levels, while the majority of HDL levels were within the low category. These findings highlight a significant cardiovascular risk among urban communities. Conclusion: This activity emphasizes that simple lipid profile screening can serve as an effective early detection tool while simultaneously providing a basis for targeted education to prevent cardiovascular disease.